Anger and Reconciliation - Koch, Bernhard (Conatus - Journal of Philosophy, 2023)
Emotions are a much-neglected aspect of contemporary peace ethics, which is surprising if only because the concept of positive peace encompasses a certain emotional commitment. Moreover, some emotions explicitly promote separation, conflict, and even violence. Anger is an ambivalent emotion that, on the one hand, evokes conflict but, on the other hand, expresses a sense of justice. Anger can be soothed by forgiveness, and forgiveness can lead to reconciliation. However, in individual ethics, the conceptual and factual connections are easier to explain than in political contexts, where collectives must be considered as actors. Martha Nussbaum recently subjected both anger and forgiveness to a well-founded critique. In contrast to this, however, a qualified defense will be made in the following.